Original Research: Potential of urinary nephrin as a biomarker reflecting podocyte dysfunction in various kidney disease models. Issue 16 (October 2016) - Wada, Yusuke; Abe, Masaki; Moritani, Hiroshi; Mitori, Hikaru; Kondo, Mitsuhiro; Tanaka-Amino, Keiko; Eguchi, Megumi; Imasato, Akira; Inoki, Yutaka; Kajiyama, Hiroshi; Mimura, Toshihide; Tomura, Yuichi
Urinary nephrin is a potential non-invasive biomarker of disease. To date, however, most studies of urinary nephrin have been conducted in animal models of diabetic nephropathy, and correlations between urinary nephrin-to-creatinine ratio and other parameters have yet to be evaluated in animal models or patients of kidney disease with podocyte dysfunction. We hypothesized that urinary nephrin-to-creatinine ratio can be up-regulated and is negatively correlated with renal nephrin mRNA levels in animal models of kidney disease, and that increased urinary nephrin-to-creatinine ratio levels are attenuated following administration of glucocorticoids. In the present study, renal nephrin mRNA, urinary nephrin-to-creatinine ratio, urinary protein-to-creatinine ratio, and creatinine clearance ratio were measured in animal models of adriamycin nephropathy, puromycin aminonucleoside nephropathy, anti-glomerular basement membrane glomerulonephritis, and 5/6 nephrectomy. The effects of prednisolone on urinary nephrin-to-creatinine ratio and other parameters in puromycin aminonucleoside (single injection) nephropathy rats were also investigated. In all models tested, urinary nephrin-to-creatinine ratio and urinary protein-to-creatinine ratio increased, while renal nephrin mRNA and creatinine clearance ratio decreased. Urinary nephrin-to-creatinine ratio exhibited a significant negative correlation with renal nephrin mRNA in almost all models, as well as a significant positive correlation with urinary protein-to-creatinine ratio and a significant negative correlation with creatinine clearance ratio. Urinary protein-to-creatinine ratio exhibited a significant negative correlation with renal nephrin mRNA. Following the administration of prednisolone to puromycin aminonucleoside (single injection) nephropathy rats, urinary nephrin-to-creatinine ratio was significantly suppressed and exhibited a significant positive correlation with urinary protein-to-creatinine ratio. In addition, the decrease in number of glomerular Wilms tumor antigen-1-positive cells was attenuated, and urinary nephrin-to-creatinine ratio exhibited a significant negative correlation in these cells. In conclusion, these results suggest that urinary nephrin-to-creatinine ratio level is a useful and reliable biomarker for predicting the amelioration of podocyte dysfunction by candidate drugs in various kidney disease models with podocyte dysfunction. This suggestion will also be validated in a clinical setting in future studies.